A complex case of autoimmune encephalitis with renal twist - A case report - Kashif Khan; Ainan Arshad; Salma Rattani (LIAQUAT MEDICAL RESEARCH JOURNAL, 2023)
Autoimmune Encephalitis (AE) presents diagnostic challenges due to its diverse symptoms. We describe a case of a 32-year-old male with fever, seizures, and altered mental status, presented at Aga Khan hospital, Karachi, Pakistan. Unusual cerebrospinal fluid findings and autoimmune markers led to AE diagnosis. Autoimmune encephalitis’s intersection with lupus nephritis required a multidisciplinary approach, resulting in significant improvement. This case highlights the importance of clinical suspicion and antibody testing in AE diagnosis and offers insights into evolving autoimmune disease management.